The Quaternary Hippopotamus records from Italy. (3rd July 2022) - Martino, R.; Pandolfi, L.
ABSTRACT: The genus Hippopotamus dispersed from Africa to Europe during the Pleistocene and the taxon is testified from different Italian localities. Despite the large number of available specimens, Hippopotamus is mainly documented by fragmentary remains and detailed stratigraphic and/or geographic data are often absent or uncertain. In Italy, hippopotamuses are recorded in at least 100 fossiliferous localities spanning from the late Early Pleistocene to the Late Pleistocene. At present, three different Pleistocene species are recognised: H. antiquus from Early to Middle Pleistocene, H. amphibius from Middle to Late Pleistocene and H. pentlandi from late Middle-early Late Pleistocene Sicilian localities. Upper Valdarno basin (Tuscany), Chiusi basin (Tuscany), Colfiorito basin (Umbria), Sant'Oreste (Latium), Puntali Cave (Sicily) and Acquedolci (Sicily) are just a few fossiliferous Italian sites where significative findings of Hippopotamus were collected during the 19th and 20th centuries.